2016
DOI: 10.1017/s0958344016000197
|View full text |Cite
|
Sign up to set email alerts
|

Exploring collaborative reverse subtitling for the enhancement of written production activities in English as a second language

Abstract: This article explores the effects of collaborative reverse subtitling as an activity for the promotion of writing skills in English as a second language. An initial analysis is undertaken of the pros and cons of the role of translation in second language learning historically and the role of information and communication technology in this process, with special attention being paid to recent initiatives on the didactic use of audiovisual translation in the form of subtitling, and the evidence of their efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
1
16
0
10
Order By: Relevance
“…The type of analysis applied is both qualitative and quantitative. Concerning reverse interlingual subtitling, the research focus is the development of writing and translation skills (Burczyńska, 2015;Talaván et al, 2016a;Talaván & Rodríguez-Arancón, 2014b). In the three experimental studies available, a qualitative and quantitative analysis is carried out on reverse subtitling of movie excerpts (with Aegisub or Subtitle Workshop) with English as the L2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The type of analysis applied is both qualitative and quantitative. Concerning reverse interlingual subtitling, the research focus is the development of writing and translation skills (Burczyńska, 2015;Talaván et al, 2016a;Talaván & Rodríguez-Arancón, 2014b). In the three experimental studies available, a qualitative and quantitative analysis is carried out on reverse subtitling of movie excerpts (with Aegisub or Subtitle Workshop) with English as the L2.…”
Section: Discussionmentioning
confidence: 99%
“…In the three experimental studies available, a qualitative and quantitative analysis is carried out on reverse subtitling of movie excerpts (with Aegisub or Subtitle Workshop) with English as the L2. Two of the studies involve a great number of university students as participants in online learning settings (Talaván et al, 2016a;Talaván & Rodríguez-Arancón, 2014b), whereas investigation on the application of intralingual subtitling tasks in language learning is quite limited. To this regard, only two studies were identified, one of which combines the use of intralingual subtitling and dubbing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En la combinación L2-L1 de subtítulos interlingüísticos (directos), es decir, la subtitulación estándar más conocida, todos los niveles de dominio de la L2 (de A1 a C2) podrán beneficiarse de la actividad, gracias al apoyo constante de la lengua materna. Cabe mencionar aquí que el uso de la traducción y de la lengua materna en este contexto resulta altamente beneficioso, al estar los alumnos inmersos en una actividad de mediación que además combina el componente tecnológico con el audiovisual (Talaván, Ibáñez, & Bárcena, 2017). Los niveles más iniciales (A1 y A2) deberán subtitular vídeos más breves y sencillos, con menor contenido lingüístico, mientras que el resto de los niveles (B1, B2, C1 y C2) podrán trabajar con mayor variedad de tipologías de vídeos y complejidades lingüísticas.…”
Section: La Subtitulación Didáctica Y La Comprensión Audiovisualunclassified